Den ikke-professionelle skuespiller som dokument? Om bekræftelse af social virkelighed i samtidsteatret. - Hinz, Melanie; Lauenstein Led, Jens Christian (Peripeti, 2014)
This article examines in theory and by the analysis of three productions whether a non-professional cast, quite often seen in contemporary documetary theatre today, could be considered and described as documents. The study includes an examination of documentary theatre in the sixties especially as defined by Peter Weiss. It also draws on recent theoretical studies such as works by Steyerl. It reaches the conclusion that documentary theatre of the sixties felt a strong belief in the veracity of the written document, where as contemporary documentary theatre oscillate between doubt and faith. This applies especially to the theatrical event of Christoph Schlingensief, Bitte Liebt Österreich!, where as Meine Akte und ich by Clemens Bechtel concentrate much more on the authenticity of the non-professional cast. In Hinz’ own performance Cash. Das Geldstück it is particulary this doubt about authenticity that attracts the attention of the audience to the documentary quality of the non-professionals.